2021
DOI: 10.3389/fnhum.2021.661392
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Analysis of Phonation in Children With Smith–Magenis Syndrome

Abstract: Complex simultaneous neuropsychophysiological mechanisms are responsible for the processing of the information to be transmitted and for the neuromotor planning of the articulatory organs involved in speech. The nature of this set of mechanisms is closely linked to the clinical state of the subject. Thus, for example, in populations with neurodevelopmental deficits, these underlying neuropsychophysiological procedures are deficient and determine their phonation. Most of these cases with neurodevelopmental defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…In this work, we propose the development of ML models that allow for the identification of SMS versus normotypic individuals. One clinical feature of the SMS pathology is voice hoarseness (Elsea and Girirajan, 2008), as described in previous studies (Hidalgo-De la Guía et al, 2021b), it has been demonstrated that by utilizing the CPP values of SMS and normotypic individuals, it is possible to create divisions into highly differentiated subgroups. This differentiation is primarily due to the hoarseness present in individuals with this genetic pathology.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…In this work, we propose the development of ML models that allow for the identification of SMS versus normotypic individuals. One clinical feature of the SMS pathology is voice hoarseness (Elsea and Girirajan, 2008), as described in previous studies (Hidalgo-De la Guía et al, 2021b), it has been demonstrated that by utilizing the CPP values of SMS and normotypic individuals, it is possible to create divisions into highly differentiated subgroups. This differentiation is primarily due to the hoarseness present in individuals with this genetic pathology.…”
Section: Discussionmentioning
confidence: 88%
“…These types of studies are necessary to improve early disease detection. Currently, the average SMS diagnosis age is approximately seven years (Hidalgo-De la Guía et al, 2021b), leading to problems for these patients. Problem arises because SMS requires specific therapies that, when implemented late, cause different kinds of delays.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations